Grounded Theory Research: Teaching for Mastery in Writing Ability as a Skill - BLASCO, David (Asian Journal of Contemporary Education, 2021)
The purpose of this study was to investigate the needs of students to improve their ability in writing essays in English. One hundred and three students were surveyed after three months after starting classes on fall semester of 2020. A qualitative research approach based on Grounded Theory was used throughout the research process. The data analysis gave rise to a process leading to a core category which shows how students can reach a higher level of writing ability as a skill. Three different categories were identified as being important for gaining a writing ability as a skill, namely, the teacher pedagogy skills, questioning strategies and individual characteristics. Instructors should organize lessons in small steps to achieve a learning goal. At the same time, they have to make sure students comprehend not only directions of learning activities but also the concepts they are working on. In addition, educators must support and encourage to each student by showing warm feelings and focusing on helping student to maintain a satisfying flow of communicative competency. If these requirements were met, students’ ability in writing essays would be increased. Writing as a skill can be reached when students feel that they are treated fairly, with patience and attention. Instructors should be aware of these needs and should treat students as individuals and thus to help them to achieve higher levels of competency.